Some Recent Developments of Microstrip Antenna - Yong Liu; Li-Ming Si; Meng Wei; Pixian Yan; Pengfei Yang; Hongda Lu; Chao Zheng; Yong Yuan; Jinchao Mou; Xin Lv; Housjun Sun (International Journal of Antennas and Propagation)
Although the microstrip antenna has been extensively studied in the past few decades as one of the standard planar antennas, it still has a huge potential for further developments. The paper suggests three areas for further research based on our previous works on microstrip antenna elements and arrays. One is exploring the variety of microstrip antenna topologies to meet the desired requirement such as ultrawide band (UWB), high gain, miniaturization, circular polarization, multipolarized, and so on. Another is to apply microstrip antenna to form composite antenna which is more potent than the individual antenna. The last is growing towards highly integration of antenna/array and feeding network or operating at relatively high frequencies, like sub-millimeter wave or terahertz (THz) wave regime, by using the advanced machining techniques. To support our points of view, some examples of antennas developed in our group are presented and discussed.